APPLICATION OF PROBLEM-BASED LEARNING MODEL (PBL) IN PJOK LESSONS TO IMPROVE CRITICAL THINKING SKILLS IN THE ERA OF DIGITALIZATION - Is, Zulheri; Subhananto, Aprian; SAIFI, Syahrianur (Sport Pedagogy Journal, 2024)
The low critical thinking of students while learning can be seen from several aspects such as the inability of students to identify a problem properly, so that the solution in learning is not resolved properly. The purpose of this study is to see the improvement of critical thinking skills through a problem-based learning model in Physical Education, Sports and Health (PJOK) learning. The research design used in this study is Quasi Experimental Design, which is a development of True Experimental Design. This research was carried out at MTsN Model Banda Aceh with the research subjects of Class VIII-1 students totaling 32 students with purposive sampling sample collection techniques. The instrument used in terms of seeing students' critical thinking skills uses a written test with true-false question types. The results of this study show that the problem base learning model is able to improve students' critical thinking skills well in physical education learning. It can be seen in the descriptive statistics of the average value of the problem base learning model of 0.91, while in conventional learning of 0.86, it means that the problem base learning model is better than conventional learning in terms of improving students' critical thinking skills in physical education.Keywords: Problem Base Learning, Critical Thinking, PJOK lessons